Long-term Euro-ASA Registry Data: Alcohol Septal Ablation Is Safe and Effective. Issue 28 (29th October 2015) - Cunningham, Muriel
Alcohol septal ablation (ASA) performed in dedicated centers is a safe and effective procedure for highly symptomatic obstructive hypertrophic cardiomyopathy patients. The post-ASA residual obstruction is a significant factor influencing long-term functional status and survival. Appropriate pre-procedural patient selection and elimination of the left ventricular outflow obstruction should be pursued in these patients.